Growth and Development Screening in Preschool-Age Children Based on Denver Development Screening Test II - Nabila Mutiarawati; Tanty Wulan Dari (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
Early detection of child growth and development deviations is a major global theme in modern child health services in the first 5 years of life. This study aims to determine the results of growth and development screening in the group A at Darma Wanita Persatuan Medalem Kindergarten with the Denver Development Screening Test II method. This study used a type of descriptive research that used total sampling with respondents as many as 25 students by using the DDST II observation sheet research instrument which then the screening results were processed in the form of data tabulation. From the research conducted, it was found that in the four sectors of growth development tasks, the results of caution and delay were the most in the language sector, namely caution 12% and delayed 4%, while personal social 1 delayed 8% and 2 delayed 4%, in the gross motor and fine motor sectors the results were 100% normal. The success of stimulation is influenced by when the initial time is given, how long, and how to do it. Some factors that can cause caution or delayed results are, lack of concentration, lack of stimulation, and children are still unfamiliar with people they just met.